(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The purpose of this research work was to formulate a fast dissolving film of Losartan potassium for the treatment of hypertension. The fast dissolving films of Losartan potassium were prepared by solvent casting technique using film forming polymer HPMC 15 and 50 cps and PEG is used as plasticizer. From the preliminary physical observation of these prepared films the best were selected for incorporation of Losartan potassium. The electron microscopy showed that the films are clear, colorless with smooth surface and little pores, without any scratches on the films. All the films prepared were evaluated for Physical appearance and surface texture, weight uniformity of films, thickness of the films, folding endurance, surface pH, drug content uniformity and in-vitro disintegration time of films all the results were found to be satisfactory. The t50% and t90% values decreased with increase in the concentration of SSG, CCS and CP. The rapid increase in dissolution of Losartan potassium with the increase in CCS. Among all the film formulation FA2 and FA8 (6% CCS HPMC 15 and 50 cps) were found to be promising and showed a disintegration time of 36 and 32 sec, respectively and 50% of drug released in 9.74 and 8.19 min, and 90% of drug released in 18.00 and 17.12 min respectively. Based on the above results it can be concluded that the fast dissolving oral film of Losartan potassium may produce the rapid action thereby enhance the absorption by avoiding the first pass effect.